PENGARUH KARAKTERISTIK KOPERASI TERHADAP PERMINTAAN JASA AUDIT EKSTERNAL: STUDI EMPIMS KOPERASI DI KOTA SEMARANG - M. Noor Ardiansah (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2011)
This research would provide an empirical impact of some variables such: size of member, organization size, gearing ratio and liquidity ratio toward demand of external audit to cooperation. This further research is done to 78 cooperation organization in Semarang area, which have annual member meeting in 2004-2005. Logistic regression used to analyses the data. Result show that, each individually or simultaneous these independent variables such size of member, organization size, gearing ratio and liquidity ratio was significant influence toward demand of external audit to cooperation. This finding was give more empirical evidence with result of Tauringana & Clark (2000) and Ardiansah (2005) that voluntary demand of external audit to cooperatioan increasing consider to extend of cooperation characteristics such size ofmember, organization size, gearing ratio and liquidity ratio